Observation the Serum Magnesium Level During Second and Third Trimester Pregnant Women - Tawfeg A. Elhisadi; Akrahm M. Saleh Habil; Azza M. Mohamed (African Journal of Advanced Pure and Applied Sciences, 2023)
Magnesium is one of the major electrolytes; Magnesium deficiency is common, especially among pregnant women which plays an important role in pregnancy for the formation of new tissues and for cell multiplication in a growing fetus and frequently overlooked in critical illness, leading to an adverse clinical outcome if not monitored regularly particularly in pregnant women. This study was conducted to observe the serum magnesium level during pregnancy because magnesium deficiency in pregnant women will leads to life threatening complications for mother as well as their babies. This observational study was conducted in the department of gynecology, Al Wahda Hospital. Derna, Libya. The inclusion criteria of the study were pregnant women with 20-46 years of age, had second and third trimester of pregnancy. The informed consent was taken from all participants participated in the study and the grouping was made according to serum magnesium level, trimester of pregnancy. The blood sample collected for serum Magnesium level and sent to laboratory for analysis. The data was analyzed in SPSS version 11.00. Total of 50 patients were selected in this study. We have observed high prevalence of hypomagnesemia 44 % among pregnant women in second and third trimester. Moreover, we found no association between serum magnesium levels and the subsequent development of hypertension during the pregnancy, as a result of non-significant p > 0.05. However, there are mild significant direct correlation of hypomagnesemia with hypotension but this relationship illogical and this hypotension due to other courses and most previous studies as we too suspect hypomagnesemia may lead to hypertension.